ERP Training: A Framework to Develop Appropriate Training to Accommodate the Variety of End-user Learning Styles in Thailand - Chayakonvikom, Monta; Cannell, Stephen (Advances in Social Sciences Research Journal, 2018)
This article proposes an ERP training framework to accommodate the various learning styles of Thai users by analyzing the current ERP training approach and the learning styles of Thai users, including learning style and cultural learning behavior, which are reflected through the training outcomes of various end-user learning style groups. A qualitative research approach was employed in this study. Semi-structured interview and questionnaire were used as instruments to collect data based on seventy-two end-users who had participated in ERP training in implementation projects at twenty-two companies in Thailand. The recommendations for an ERP training framework were developed based on four dimensions of the current approach, which largely failed to accommodate Thai users’ various learning styles. This framework would help to improve ERP training quality, which is a key success factor in ERP implementation.